Effect of cold atmospheric pressure plasma treatment of eggshells on the total bacterial count inoculated Salmonella Enteritidis and selected quality parameters. Issue 1 (3rd June 2020) - Moritz, Maike; Wiacek, Claudia; Weihe, Thomas; Ehlbeck, Jörg; Weltmann, Klaus‐Dieter; Braun, Peggy G.
Abstract: In the European Union, foodborne outbreaks caused by Salmonella Enteritidis, related to eggs and egg products, have even been reported in 2018. Atmospheric pressure plasma is becoming increasingly important as a decontamination method. A semidirect cold atmospheric pressure plasma, the flexible electrode plasma source, was developed for treating whole hen's eggs. An average reduction of 1.16 and 0.95 log colony‐forming units (CFU)/egg was achieved for the total bacterial count of clean and dirty eggs, respectively. An inactivation of 4.1 log CFU/egg Salmonella Enteritidis was achieved with artificially inoculated eggshells. Selected quality parameters and sensory properties were analysed. Overall, the present study yielded promising results for a realistic implementation of an industrial prototype plasma source. Abstract : A semidirect flexible electrode plasma source was tested as a new decontamination method for whole hen's eggs. The effective inactivation of artificial Salmonella Enteritidis contamination was realised, and no influence on selected quality parameters could be detected. Slight variances were revealed by the first‐time sensory testing, thus requiring further optimisation of the plasma source.